Climate change effects on food security in Tajikistan - Khakimov, Parviz; Aliev, Jovidon; Thomas, Timothy S.; Ilyasov, Jarilkasin; Pechtl, Sarah; Dunston, Shahnila (International Food Policy Research Institute, 2024)
Climate change is one of the main challenges for food security in Tajikistan in the medium and long term. Tajikistan’s Agri-Food System and Sustainable Development Program (ASDP) for the period up to 2030 defined food and nutrition security as one of six priorities. Additionally, climate change is one of the key obstacles to the achievement of the country’s strategic objective defined in the National Development Strategy (NDS) 2016–2030, which is to improve the living standards of the population, and one of the four strategic priorities, which is to ensure food security and access to quality nutrition by 2030.